Methadone Flexi Dispensing (MFlex) Intelligence System utilizing the Mahalanobis-Taguchi System - Pinueh, N.S.; Abu, Mohd Yazid; S K M, Saad; N.H, Aris; Sari, E. (Penerbit UMP, 2023)
Patients who are participating in the methadone flexi dispensing (MFlex) program are obliged to provide their blood samples for various testing, such as lipid profiles. A doctor evaluates three parameters, including cholesterol, HDL cholesterol, and LDL cholesterol to determine whether or not the patient has a lipid issue. Since, the current structure lacks an ideal atmosphere for classification and optimization caused by inaccuracies in measurement methodologies and a lack of explanation for significant aspects that have an effect on the accuracy of diagnostics. The objective is to implement the Mahalanobis Taguchi system (MTS) in the MFlex program. Utilizing a total of 34 parameters, there are two different types of MTS techniques used for classification and optimization: the RT method and T method. The average Mahalanobis distance (MD) for healthy conditions is 1.0000 whereas for unhealthy is 79.5876. As a result, there is 19 parameters indicate a positive degree of contribution. 15 unknown samples were diagnosed with a variety of positive and negative degree of contribution to achieving a lower MD. Type 5 of 6 alterations was chosen as the best suggested possibility. In conclusion, MTS is able to be applied in medical environment.